Synthesis and Characterization of Naphthalene-Based Banana- Shaped Liquid Crystals for Photoswitching Properties - Hegde, Gurumurthy; Lutfor, M. R.; M. M., Yusoff; Muhammad Nor Fazli, Abd Malek; Nurlin, Abu Samah; Srinivasa, H. T.; Kumar, Sandeep (John Wiley & Sons, Inc., 2014)
A series of banana-shaped monomers containing naphthalene as central units, azobenzene in side arms with terminal alkenes were synthesized and characterized. Polarizing optical microscopy, DSC and X-ray diffraction measurements reveal that one compound processes a nematic phase while other four compounds exhibit B6 phase. The absorption spectrum of trans-azobenzene displays high-intensity -* transition at 365 and low-intensity n-* transition at 450 nm. These molecules exhibit strong photoisomerisation behaviour in solutions in which trans to cis isomerisation takes 55 seconds whereas reverse process takes about 32 hours. Such a long thermal back relaxation is useful for creation of optical image storage devices.